2003
DOI: 10.1051/agro:2003228
|View full text |Cite
|
Sign up to set email alerts
|

Use of a pre-sidedress soil nitrate test (PSNT) to determine nitrogen fertilizer requirements for irrigated corn

Abstract: -In the present study, a 2-year N rate response experiment was conducted in different fields to monitor NO 3 -N soil profiles, N accumulation by the crop and final crop performance, in order to assess if soil NO 3 -N at pre-sidedressing (Pre-Sidedress Soil Nitrate Test, PSNT) is a reliable indicator for soil N availability for corn in the irrigated area served by canal d'Urgell (Lleida, Spain), and if the test can be used to separate responsive fields from non-responsive fields to sidedress N fertilizer applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…Our research has focused on the use of pig slurry (Guillaumes et al, 2006), the use of soil and plant tests (Ferrer et al, 2003), especially soil nitrate before N fertilization, and on the use of new fertilizers that aim to improve the efficiency of N use and minimize environmental impacts.…”
Section: Economicsmentioning
confidence: 99%
“…Our research has focused on the use of pig slurry (Guillaumes et al, 2006), the use of soil and plant tests (Ferrer et al, 2003), especially soil nitrate before N fertilization, and on the use of new fertilizers that aim to improve the efficiency of N use and minimize environmental impacts.…”
Section: Economicsmentioning
confidence: 99%
“…The previously cited critical soil nitrate contents (CNC) to produce the maximum corn yields were predominantly obtained under relatively fertile soils (Mollisols and Alfisols) under rainfed conditions of the Midwest or in Argentina. However, few studies tested whether the previously reported CNC would also be valid for irrigated Mediterranean environments, which are characterized by a semiarid climate, poorly developed soils (Inceptisols and Entisols), and irrigation (Spellman et al, 1996; Villar et al, 2000; Ferrer et al, 2003; Berenguer et al, 2009). Under similar conditions, the CNC were established at 13 to 15 mg NO 3 –N kg –1 (PSNT, 0–30‐cm depth) for a yield goal of 7 to 11 Mg ha –1 (Spellman et al, 1996); at 21 to 32 mg NO 3 –N kg –1 (PSNT, 0–30‐cm depth) for a yield goal of 10 Mg ha –1 (Villar et al, 2000), and at 45 mg NO 3 –N kg –1 (PSNT + N fertilization, 0–30‐cm depth) for a yield goal of 14 Mg ha –1 (Ferrer et al, 2003).…”
mentioning
confidence: 99%
“…Previous studies about soil nitrate tests have mainly focused on three tests: PPNT (Bundy and Malone, 1988; Schmitt and Randall, 1994); the PSNT (Magdoff et al, 1984; Magdoff, 1991; Fox et al, 1989; Vanotti and Bundy, 1994); and the available soil N, which was defined as the PPNT or PSNT plus N applied with commercial fertilizer (Villar‐Mir et al, 2002; Ferrer et al, 2003; Halvorson et al, 2006). Preplant nitrate test samples are taken in early spring from the upper 30, 60, or 90 cm of the soil and the carryover of mineral N from previous crops is quantified.…”
mentioning
confidence: 99%
“…However, in areas with low winter precipitation, as in large parts of California, NO 3 − is often not leached from the root zone with winter rains, and soil NO 3 − present in spring may therefore either be carryover NO 3 − from the previous crop or soil N mineralized in early spring (Zebarth et al 2009). Under these conditions, spring NO 3 − -N cannot be used to predict N mineralization during the growing season, resulting in a weak relationship between the test results and total N available for crop uptake (Cela et al 2013;Ferrer et al 2003;Spellman et al 1996;Villar et al 2000).…”
Section: Pre-sidedress No 3 − Test (Psnt)mentioning
confidence: 99%
“…When winter rainfall is low, PSNT thresholds proposed in the research literature for irrigated corn have been inconsistent, ranging from 13 to 50 ppm in different studies (Cela et al 2013;Ferrer et al 2003;Spellman et al 1996;Villar et al 2000). These inconsistencies are likely due to high NO 3 − concentrations in the soil profile below the top foot (Spellman et al 1996), leaching losses with irrigation water (Magdoff 1991) or low N mineralization potentials of the soils.…”
Section: Pre-sidedress No 3 − Test (Psnt)mentioning
confidence: 99%